Greenfield project finance loan maturity and the role of multilateral development banks in developing countries - Yasumura, Kota (The Economics and Finance Letters, 2023)
This paper is intended to provide empirical evidence for the financial additionality of multilateral development banks (MDBs) in private sector infrastructure projects. To validate MDBs’ financial additionality, this study uses IJGlobal’s project finance database to examine whether the loan tenor of MDBs’ project finance loans is significantly longer than the average loan tenor extended by commercial banks, using ordinary least squares (OLS) and Poisson Pseudo Maximum Likelihood (PPML) estimations. The result of the empirical analysis shows that project finance loans involving MDBs have significantly longer loan maturity than average loans in lower-middle-income and upper-middle-income countries, while projects in low-income countries and Sub-Saharan Africa do not have such a tendency. Furthermore, in host countries where government effectiveness is underdeveloped, the coefficient of project finance loans provided by MDBs is negative with statistical significance. As a policy implication, these findings indicate that for MDBs to ascertain financial additionality in countries where government effectiveness is weak, additional measures such as capacity building of the host government and additional financial intervention are needed.